Human Formation of the Educator during a Pedagogy Undergraduate Course - outcomes of an exploratory research study - Ximenes, Lavínia de Melo e Silva; Policarpo Junior, José; Wanderley, André Leite (Advances in Social Sciences Research Journal, 2017)
This article is a result of an exploratory research study on the feasibility and comprehensiveness of the undergraduate course in Pedagogy promoting the human formation of the educator. The idea of human formation aims to provide the appropriate formation of all constituent aspects of a human being in an undivided way, which includes the formation of cognition, the senses, corporeity, habits, emotional life, the cultivation of relationships and of reflection on the personal meaning of singular human life, and furthermore to understand education itself as a fundamental mediation of formation. In order to verify whether or not the undergraduate course in Pedagogy promotes such training, a convenience sample which consisted of 253 students enrolled in that course at the Federal University of Pernambuco (UFPE), who included first year and final year undergraduates, were interviewed in 2011. A 5-point Likert scale with 41 items was drawn up and called the Scale of Human Formation of the Educator (SHFE). This scale was divided into three sub-scales which were designed to assess: (a) the personal and relational development of the student; (b) understanding the role of the educator, and; (c) the formative understanding of education, school and pedagogy. Statistical tests were carried out to compare the averages of first- and final-year students who were assessed by the three subscales mentioned. It was postulated as a hypothesis that this course would not promote the human formation of the students in accordance with the terms referred to. The results achieved by the research have partially refuted the hypothesis that was formulated, although the differences achieved are not of a significant amplitude.